Performance of diesel engine with biodiesel fuel from cooking oil - Marlinda Marlinda; Suparno Suparno; Ramli Ramli; M. Irwan; M. K. Yandi (Konversi, 2023)
Biodiesel from used cooking oil is a very potential material to replace diesel fuel. Besides being cheap, it can also reduce waste. The purpose of the study was to determine the performance of the Nissan SD22 diesel engine on the use of biodiesel as fuel and the optimum composition of biodiesel and diesel mixtures. The results of the diesel engine performance show that a high rotational speed of 2800 rpm could produce a torque of 112 N.m at B10, while the results for the power parameter at a rotational speed of 2750 rpm produced a large power of 33.46 KW for B10. As for fuel consumption for a rotation speed of 2750 rpm, B10 fuel provided 0.293 kg/(kW.hour) of specific fuel while Pertamina Dex requires 0.310 kg/(kW.hour) of specific fuel, meaning that the use of B10 saved 5.48% more than B10. As for fuel consumption for a rotation speed of 2750 rpm, B10 fuel provides 0.293 kg/kW.hour of specific fuel while Pertamina Dex requires 0.310 kg/kW.hour of specific fuel, meaning that the use of B10 saves 5.48% more than B10. Biodiesel B10 is able to provide good performance for use as a diesel engine fuel. The resulting gas emissions are smaller than diesel emissions. This proves that biodiesel is an environmentally friendly fuel.